miRNA-130b is required for the ERK/FOXM1 pathway activation-mediated protective effects of isosorbide dinitrate against mesenchymal stem cell senescence induced by high glucose - XU, JIANFENG (Int J Mol Med, 2015)
The present study was carried out to investigate the hypothesis that organic nitrates can attenuate the senescence of mesenchymal stem cells (MSCs), a superior cell source involved in the regeneration and repair of damaged tissue. MSCs were treated with high glucose (HG) in order to induce senescence, which was markedly attenuated by pre-treatment with isosorbide dinitrate (ISDN), a commonly used nitrate, as indicated by senescence-associated galactosidase (SA-β-gal) activity, p21 expression, as well as by the mRNA levels of DNA methyltransferase 1 (DNMT1) and differentiated embryo chondrocyte expressed gene 1 (DEC1), which are senescence-related biomarkers. It was also found that the senescent MSCs (induced by HG glucose) exhibited a marked downregulation in ERK activity and forkhead box M1 (FOXM1) expression, which was reversed by ISDN preconditioning. Of note, the inhibition of ERK phosphorylation or the downregulation of FOXM1 statistically abolished the favourable effects of ISDN. In addition, the investigation of the senescence-associated miR-130 family suggested that miR-130b mediates the beneficial effects of ISDN; it was found that the protective effects of ISDN against the senescence of MSCs were prominently reversed by the knockdown of miR-130b. Furthermore, the downregulation of ERK phosphorylation or FOXM1 expression decreased the miR-130b expression level; however, the suppression of miR-130b demonstrated no significant impact on ERK phosphorylation or FOXM1 expression. Taken together, to the best of our knowledge, the present study is the first to demonstrate the favourable effects of ISDN against HG-induced MSC senescence, which are mediated through the activation of the ERK/FOXM1 pathway and the upregulation of miR-130b.